Born in the fire: what we can learn from how digital publishers in the global south approach platforms - Nielsen, R; Cherubini, F (Reuters Institute for the Study of Journalism, 2022)
Based on interviews with a strategic sample of 11 publishers in eight low- and middle-income countries, in this report we analyse how various digital publishers across a range of Global South countries approach digital platforms: both big platform companies such as Google and Meta; rapidly growing ones, including TikTok; and smaller ones such as Twitter and Telegram.